Penggunaan metronom untuk optimalisasi pelatihan resusitasi jantung paru dengan manekin: A systematic literature review - Rismah, Rismah; Purnawan, Iwan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Cardiopulmonary Resuscitation (CPR) is an emergency action that is very important to increase the chances of survival of someone who experiences cardiac arrest. CPR guidelines generally recommend a specific chest compression rate of around 100-120 compressions per minute. The metronome provides consistent sound guidance, helping trainees measure and maintain the correct pace during practice. This can reduce the risk of errors in providing inadequate chest pressure. Purpose: To assess whether use of a metronome can improve participants' skills in maintaining chest compression rates in accordance with CPR guidelines. Method: Systematic literature review (SLR) databases PubMed and Google Scholar use the keywords chest compression, metronome, and cardiopulmonary resuscitation. Researchers determined relevant and specific questions to dig deeper into this problem,